Intervensi Triase Perawat Instalasi Gawat Darurat Terhadap Akurasi Penentuan Prioritas Pasien - Sinaga, Hotma Romaida; Iksan , Ricky Riyanto; Yeni, Roza Indra (Borneo Nursing Journal (BNJ), 2026)
The Emergency Department (ER) requires fast and accurate clinical decision-making, especially in the triage process to determine patient care priorities. Inaccurate triage can cause delays in the treatment of critical patients, so it is necessary to improve nurse competency through triage education and training. This study aims to analyze the effectiveness of triage education and training interventions on improving the accuracy of patient prioritization by ER nurses. This study used an Evidence Based Nursing design with a pre-test and post-test approach. The intervention was carried out on 4 ER nurses at Hospital X on May 18–21, 2026. Respondents were selected based on inclusion criteria, namely nurses who actively perform triage and are willing to participate in the activity. Data were collected using a triage knowledge questionnaire and an observation sheet on the accuracy of triage implementation based on standard operating procedures. Data analysis was performed using a Paired t-test. Before the intervention, all respondents (100%) were in the inaccurate triage accuracy category with an average score of 20.60 ± 4.682. After receiving triage education and training, all respondents (100%) demonstrated correct accuracy, with an average score increasing to 30.80 ± 5.812. Statistical test results showed a significant difference between before and after the intervention, with a p-value of 0.001. Conclusion: Triage education and training effectively improved the accuracy of patient prioritization by emergency department nurses. This intervention can be implemented as a strategy to improve nurse competency in supporting patient safety and the quality of emergency care.